Penerapan Metode Min-Max Dengan Reminder Pada Inventory Control Di Toko Obat - Yurindra, Y; Fitriyani, F; Mayasari, Melati Suci; Kirana, Chandra; Anisah, A (Brahmana : Jurnal Penerapan Kecerdasan Buatan, 2023)
Inventory of goods is one of the supports in meeting the survival of a company. One of them is in business units related to the health sector, namely pharmacies and drug stores. One of them is Toko Herbal 99, which is a drug store that sells various herbal products. Many problems were found at the drugstore, among others, transaction documentation that had not been computerized and goods inspections were still carried out manually and resulting in frequently missed conditions of out-of-stock items or vacancies without being quickly identified. The min-max method is one method that can be used to solve this problem by making good inventory planning. By determining the minimum and maximum points for the number of items and making notifications or reminders for the warehouse admin, this method will be able to improve the performance of the herbal medicine shop 99 which has been a problem. This model is supported by a Desktop-based inventory control application design. With the application of the min-max method on the inventory control application, it is expected to make it easier to manage stock items and minimize the occurrence of stock shortages.